TRANSFORMATIONAL LEADERSHIP IN ISLAMIC BOARDING SCHOOLS DURING AND AFTER COVID-19: STRENGTHENING INSTITUTIONAL GOVERNANCE IN TIMES OF CRISIS - Suryana, Aep Tata (Ikatan Dosen Menulis, 2021)
The COVID-19 pandemic has caused significant disruptions to the institutional governance of Islamic boarding schools, which had been operating stably. The uncertainty of the situation, restrictions on activities, and pressure on the education system test the resilience of the leadership structure in the Islamic boarding school environment. In this context, the role of leadership becomes crucial in determining the direction of response, adaptation, and institutional consolidation. This study aims to explore how transformational leadership in Islamic boarding schools can strengthen institutional governance during and after a crisis. The method used is a qualitative approach with data collection through literature studies of various relevant sources. Data are analyzed interpretively to reveal thematic patterns that reflect the leadership process during the pandemic. The results of the study show that Islamic boarding school leaders responded to the crisis with a strategy of rapid decision-making, reorganization of structures, and adaptive operational adjustments. During the recovery period, institutional consolidation occurred which was marked by structural transformation and strengthening of the coordinating function. In addition, leadership also encourages innovation and independence, both in terms of education, economy, and external institutional relations.